A new idiocerine leafhopper genus, Dianica, from China (Hemiptera: Cicadellidae) - Zhang, Bin (Zootaxa, 2018)
The new idiocerine leafhopper genus Dianica gen. nov. is described and illustrated based one species, Dianica rugulosa sp. nov. from southwestern China. A diagnosis of the new genus is given and compared to the related genera. In addition, a key to genera and a checklist of species for Tasnimocerus group are also provided.